2021
DOI: 10.3389/fmed.2021.720647
|View full text |Cite
|
Sign up to set email alerts
|

The Global Prevalence of Daptomycin, Tigecycline, and Linezolid-Resistant Enterococcus faecalis and Enterococcus faecium Strains From Human Clinical Samples: A Systematic Review and Meta-Analysis

Abstract: Background and Aim: The predominant species of the Enterococcus, Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium) cause great variety of infections. Therefore, the expansion of antimicrobial resistance in the Enterococcus is one of the most important global concerns. This study was conducted to investigate the prevalence of resistance to linezolid, tigecycline, and daptomycin among enterococcal strains isolated from human clinical specimens worldwide.Methods: Several databases includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In the present investigation, 34.95% of isolates sensitive to tigecycline were found, even though usually higher percentages of susceptible strains have been detected both in humans and domestic animals [ 42 , 43 ]. The tet genes were found to be equally distributed among susceptible, intermediate, and resistant isolates, confirming that these genes are not involved in tigecycline resistance [ 31 ].…”
Section: Discussionmentioning
confidence: 75%
“…In the present investigation, 34.95% of isolates sensitive to tigecycline were found, even though usually higher percentages of susceptible strains have been detected both in humans and domestic animals [ 42 , 43 ]. The tet genes were found to be equally distributed among susceptible, intermediate, and resistant isolates, confirming that these genes are not involved in tigecycline resistance [ 31 ].…”
Section: Discussionmentioning
confidence: 75%
“…Enterococcus faecalis is normally found in the human gastrointestinal tract and is often found associated with laboratory Drosophila (Cox and Gilmore, 2007;Broderick and Lemaitre, 2012;Loch et al, 2017) (this study). Of the five species described above that were cultured from mated females, Enterococcus faecalis was chosen for further study because of its ease of culture, frequent association with Drosophila, and its relevance to human health (Kao and Kline, 2019;Dadashi et al, 2021). To determine whether Enterococcus faecalis might affect life span and interact with mifepristone in vivo, adult females were assayed for life span using control media and media supplemented with Enterococcus faecalis in the presence or absence of mifepristone.…”
Section: Supplementation Of Media With Enterococcus Faecalis Has No E...mentioning
confidence: 99%
“…In 2021, Dadashi et al reported that the global prevalence of E. faecium among enterococcal isolates from clinical infections was 40.6%, with 43.6 % in Asia, 38.0 % in Europe, and 36.8 % in America [21].…”
Section: Introductionmentioning
confidence: 99%